ASSEMBLY AND AGGREGATION OF TOBACCO MOSAIC VIRUS IN TOMATO LEAFLETS - Shalla, Thomas A. (The Rockefeller University Press, 1964)
Cells of tomato leaflets (Lycopersicum esculentum Mill.) were studied by phase and electron microscopy at various intervals after inoculation with a common strain of tobacco mosaic virus (TMV). Forty-eight hours after inoculation, prior to the development of assayable virus, individual TMV particles, and also particle aggregates, were observed in the ground cytoplasm of mesophyll cells. The most rapid synthesis of virus occurred between 80 and 300 hours after inoculation. Cytological changes during this time were characterized by an increased number of individual particles in the cytoplasm, growth of some aggregates, distortion and vacuolation of chloroplasts, and formation of filaments in the cytoplasm which were approximately four times the size of TMV. These filaments were interpreted as possible developmental forms of the TMV particle. Vacuoles in chloroplasts commonly contained virus particles. Evidence indicated that TMV was assembled in the ground cytoplasm and, in some cases, subsequently was enveloped by distorted chloroplasts.